Bodies of information
1 online resource.
Keywords: "Bodies of Information initiates the Routledge Advances in the History of Bioethics series by encompassing interdisciplinary Bioethical discussions on a wide range of descriptions of bodies in relation to their contexts from varying perspectives: including literary analysis, sociology, criminology, anthropology, osteology and cultural studies, to read a variety of types of artefacts, from the Romano-British period to Hip Hop. Van Renslaer Potter coined the phrase Global Bioethics to define human relationships with their contexts. This and subsequent volumes return to Potter's founding vision from historical perspectives, and asks, how did we get here from then?"--